Turbulent Impinging Jets into Porous Materials - de Lemos, Marcelo J.S (SpringerBriefs in Computational Mechanics, 2012)
This short book deals with the mathematical modeling of jets impinging porous media. It starts with a short introduction to models describing turbulences in porous media as well as turbulent heat transfer. In its main part, the book presents the heat transfer of impinging jets using a local and a non-local thermal equilibrium approach.